The problem of solid waste: origins, composition, disposal, recycling, and reusing - Ibrahim Khalid; Sadiq Ullah; Iqbal Saeed Umar; Heri Nurdiyanto (Utan Kayu Publishins, 2022)
Solid waste disposal is a major challenge in many industrialized and developing nations, both in metropolitan regions as well as rural ones. The collection and disposal of municipal solid waste (MSW) is a serious issue facing metropolitan areas in many nations today. An effective MSW management strategy must satisfy all of these criteria: financial viability; technical feasibility; social and legal acceptability; and ecological friendliness. Small and large cities alike have a major difficulty in dealing with solid waste management. One of the current study topics is the valuation of food organic waste. Existing waste disposal methods include the typical landfill, incineration, composting, and other methods of handling solid waste. Composting and anaerobic digestion have traditionally been the most widely employed methods for the treatment and exploitation of the organic part of MSW (AD). The amount of organic solid waste (OSW) being generated globally is rising at an astronomical rate. Agricultural waste, domestic food waste, human and animal wastes, etc. comprise the majority of OSW. They're often used as animal feed, disposed of in landfills, or burnt. OAWs are made up of protein-, mineral-, and sugar-rich components that may be employed as substrates or raw materials in other processes.